Fear in general populations: A cross-sectional study on perceived fear of common diseases, COVID-19, life events, and environmental threats in 30 countries - Li, Jiaying; Pandian, Vinciya; Fong, Daniel Yee Tak; Lok, Kris Yuet Wan; Wong, Janet Yuen Ha; Ho, Mandy Man; Choi, Edmond Pui Hang; Davidson, Patricia M.; Duan, Wenjie; Tarrant, Marie; Lee, Jung Jae; Lin, Chia-Chin; et al. (International Society of Global Health, 2024)
Background In this study, we assessed the general population’s fears towards various diseases and events, aiming to inform public health strategies that balance health-seeking behaviours. Methods We surveyed adults from 30 countries across all World Health Organization (WHO) regions between July 2020 and August 2021. Participants rated their fear of 11 factors on an 11-point Likert scale. We stratified the data by age and gender and examined variations across countries and regions through multidimensional preference analysis. Results Of the 16 512 adult participants, 62.7% (n = 10 351) were women. The most feared factor was the loss of family members, reported by 4232 participants (25.9%), followed by cancer (n = 2248, 13.7%) and stroke (n = 1416, 8.7%). The highest weighted fear scores were for loss of family members (mean (Formula presented.), standard deviation (SD) = 3.04), cancer (= 7.00, SD = 3.09), and stroke (Formula presented., SD = 3.24). The least feared factors included animals/insects (Formula presented., SD = 2.96), loss of a mobile phone (Formula presented., SD = 2.98), and social isolation (Formula presented., SD = 3.13). Coronavirus disease 2019 (COVID-19) was the sixth most feared factor (Formula presented., SD = 2.92). Multidimensional preference analyses showed distinct fears of COVID-19 and job loss in Australia and Burundi. The other countries primarily feared loss of family members, cancer, stroke, and heart attacks; this ranking was consistent across WHO regions, economic levels, and COVID-19 severity levels. Conclusions Fear of family loss can improve public health messaging, highlighting the need for bereavement support and the prevention of early death-causing diseases. Addressing cancer fears is crucial to encouraging the use of preventive services. Fear of non-communicable diseases remains high during health emergencies. Top fears require more resources and countries with similar concerns should collaborate internationally for effective fear management.